INTERRELATIONSHIP BETWEEN SMALL SCALE AND LARGE SCALE INDUSTRY WITHIN THE INDONESIAN CULTURAL AND ART - Sobarsah Kosasih (Universitas Trisakti, 2010)
The purpose of this paper is to report the result of a study aimed at the interrelationship between small scale indusry (SSI’s) and large scale industri (LSI’s) in Indonesia. The role of the SSI’sabsorbed 83,6 million workers (Bapenas, 2005) is very important but its survival could be linked with its input and its output. As Indonesia occupied by more than 300 etnics, it is very possibleif the SSI’s survival is linked to Indonesia cultural and art. Data were collected from around 200 companies that have linkage with almost the whole Metallurgical Industries in Indonesia both the large and the small one. System approach and multiple regression were used to analysis the relationship between the SSI’s and the LSI’s. The survival of the SSI’s and LSI’s has no different in concept, but in practice, they may not be met as the different ability to coordinate production factors. communication between them has yet to be the method for exchange information. The government’s role which previously predicted has a strong influence to this cooperation appear very weak. The study indicates that the interrelationship between the LSI’s and the SSI’s is very possible if the Indonesian economy is developed based on tourist industry. The study based on the data collected within metallurgical industry might be less representative to reflect the relationship between the LSI’s and SSI’s throughout industries. This study has contributed to develope an interrelationship between the SSI’s and the LSI’s based on sistem approach which involve the cultural environment